Health, safety, and well‐being through ethical behaviours in computer and information systems development and deployment. Issue 3 (16th August 2019) - Rahanu, Harjinder; Georgiadou, Elli; Siakas, Kerstin; Ross, Margaret
Abstract: Literature on systems development has been progressively identifying the importance of social aspects in systems development. However, there is often a failure of participants in the recognition, and fulfilment, of ethical duties concerning the concepts of health, safety, and well‐being. A rational appeal can be made to normative defensible ethical rules in order to arrive at a judicious, morally justifiable judgement. In this paper, our first step is to report on the findings of a literature review, which presents the current health and safety issues concerning usage of computers in organisations and the workplace. Building on our earlier research on basic generic deontological and teleological moral principles and theories, we prescribe a set of moral rights and duties that must be exercised and fulfilled by stakeholders in systems development in order for them to exhibit moral behaviour. By identifying, and recommending a set of defensible moral obligations that must be fulfilled in the development and deployment of systems, protagonists—such as, project managers, software engineering teams, systems analysts, and clients—can fulfil their ethical duties, thus increasing the likelihood of deployed systems that are compliant with principles of health, safety, and well‐being of its users. Abstract : Participants in systems development and deployment often fail to recognise and fulfil ethical duties concerning health, safety, and well‐being. By identifying and recommending a set of defensible moral obligations that must be satisfied, protagonists, eg, project managers, software engineering teams, systems analysts, clients, etc can fulfil their proper duties, thus increasing the likelihood that a deployed system is compliant with principles of health, safety, and well‐being of its users. Ultimately delivered systems must be underpinned with ethical consideration.